A Note on Resistance Distances of Graphs - Sun, Wensheng; Yang, Yujun (Frontiers in Physics, 2022)
Let G be a connected graph with vertex set V(G). The resistance distance between any two vertices u,v V(G) is the net effective resistance between them in the electric network constructed from G by replacing each edge with a unit resistor. Let SV(G) be a set of vertices such that all the vertices in S have the same neighborhood in G-S, and let G[S] be the subgraph induced by S. In this note, by the {1}-inverse of the Laplacian matrix of G, formula for resistance distances between vertices in S is obtained. It turns out that resistance distances between vertices in S could be given in terms of elements in the inverse matrix of an auxiliary matrix of the Laplacian matrix of G[S], which derives the reduction principle obtained in [J. Phys. A: Math. Theor. 41 (2008) 445203] by algebraic method.